Fell type topologies of quasi-pseudo-metric spaces and the Kuratowski-Painlevé convergence - Jesús Rodríguez-López (Applied General Topology, 2001)
We study the double Fell topology when this hypertopology is constructed over a quasi-pseudo-metric space. In particular, its relationship with the Wijsman hypertopology is studied. We also propose an extension of the Kuratowski-Painlevé convergence in the bitopological setting.